Gay's Men : mensuel gratuit. (Liège Bruxelles : Thierry Nopens, 1984)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijks
Redactie : 16 Bergerue, 4000 Liège ; vanaf (1985) 10 : rue du Trône, 172, 1050 Bruxelles
Frans
Periodiek
Keywords: homobladen